Optimization of Gold Thin Films Thicknesses in Enhancing SPR Response - Murat N.F.; Mukhtar W.M.; Rashid A.R.A.; Dasuki K.A.; Yussuf A.A.R.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus